2022
DOI: 10.1186/s13018-022-03143-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of oblique lumbar interbody fusion (OLIF) augmented with different types of instrumentation: a finite element analysis

Abstract: Background To explore the biomechanical differences in oblique lumbar interbody fusion (OLIF) augmented by different types of instrumentation. Methods A three-dimensional nonlinear finite element (FE) model of an intact L3-S1 lumbar spine was built and validated. The intact model was modified to develop five OLIF surgery models (Stand-alone OLIF; OLIF with lateral plate fixation [OLIF + LPF]; OLIF with unilateral pedicle screws fixation [OLIF + UPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
5
22
0
Order By: Relevance
“…The BPS model had greater limitations than the UPS model in all motions. These results are consistent with the findings of previous studies 28,29 . The results of this study suggested that, compared with the SA model, all supplemental fixation modalities enhanced the stability of the lumbar spine structure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The BPS model had greater limitations than the UPS model in all motions. These results are consistent with the findings of previous studies 28,29 . The results of this study suggested that, compared with the SA model, all supplemental fixation modalities enhanced the stability of the lumbar spine structure.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the findings of previous studies. 28,29 The results of this study suggested that, compared with the SA model, all supplemental fixation modalities enhanced the stability of the lumbar spine structure. A literature review by Oxland et al 30 found that the addition of posterior instrumentation to the interbody spacer significantly increased structural stability, regardless of cage insertion trajectory or screw type.…”
Section: Effects Of All Surgical Models On Rom Of Segmentmentioning
confidence: 71%
“…Therefore, this is consistent with broken nails caused by stress fatigue in some patients after long-term activity. [37][38][39] This experiment verified that the pedicle screw internal fixation system has an obvious effect on the lumbar spine and that role in maintaining stability can reduce the probability of spinal instability. In this experiment, both models produced stress concentration at the root of the screw and the connection of the screw rod, which is consistent with the position of internal fixation failure and fracture commonly observed in the clinic.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, this is consistent with broken nails caused by stress fatigue in some patients after long-term activity. [37–39]…”
Section: Discussionmentioning
confidence: 99%
“…Five supplemental fixations established for OLIF surgical model previously [ 25 ], was evaluated on osteoporotic lumbar spines: standalone OLIF; OLIF with lateral plate fixation (OLIF + LPF); OLIF with translaminar facet joint fixation and unilateral pedicle screw fixation (OLIF + TFJF + UPSF); OLIF with unilateral pedicle screw fixation (OLIF + UPSF); and OLIF with bilateral pedicle screw fixation (OLIF + BPSF). We simulated surgery on the L4-L5 segment (Fig.…”
Section: Methodsmentioning
confidence: 99%